2018
DOI: 10.4314/iijikm.v9i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and use of massive open online courses among academic librarians in Ogun state, Nigeria

Abstract: The dynamism of the current digital era requires academic librarians to be lifelong learners who can take advantage of available opportunities to improve their professional competence continuously. Massive Open Online Courses (MOOCs) are online learning platforms that provide training to learners at little or no costs. While it is documented that a lot of Africans participate in MOOCs, it is not certain whether academic librarians in Nigeria are aware of and take full advantage of MOOCs. The study surveyed awa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…A study with librarians in Nigeria revealed that 60% were aware of MOOCs (Soyemi & Babalola, 2018), which could be interpreted as a low number in relative terms given that librarians ought to be familiar with digital resources. In a study with Greek teachers, 32% said they knew nothing about MOOCs, and a further 24% said they had heard of MOOCs but did not know what the term meant (Bakogianni et al, 2020).…”
Section: Awareness Of Moocsmentioning
confidence: 99%
“…A study with librarians in Nigeria revealed that 60% were aware of MOOCs (Soyemi & Babalola, 2018), which could be interpreted as a low number in relative terms given that librarians ought to be familiar with digital resources. In a study with Greek teachers, 32% said they knew nothing about MOOCs, and a further 24% said they had heard of MOOCs but did not know what the term meant (Bakogianni et al, 2020).…”
Section: Awareness Of Moocsmentioning
confidence: 99%
“…Technology awareness has positively influenced behavioural intention in utilizing MOOCs. The technology awareness of massive open online courses among academic librarians in Ogun state, Nigeria, influences the behavioural intention to use the technology [62]. Thus, technology awareness is a significant determinant of student's intention to use MOOCs, and technology awareness of the individual determines students' perception.…”
Section: 7mentioning
confidence: 99%